FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENERIMAAN PAJAK BUMI DAN BANGUNAN DI KABUPATEN BERAU - Dwi, Dhian (PRODI EKONOMI PEMBANGUNAN, STIE MUHAMMADIYAH TANJUNG REDEB, 2019)
Tax has a very important role in the life of the state, especially in continuing development, because taxation is one source of state revenue to finance state expenditure. Financing the implementation of government, development and society in the area of Berau Regency needs to be created with maximum efforts to extract sources of revenue and potential utilization owned by the region, one of which is through the Land and Building Tax (PBB). Strategies to increase regional revenue, including the need to know the factors that influence the PBB revenue. This study aims to analyze what factors influence the receipt of land and building tax (PBB) in Berau Regency. The data used in this study are time series data with an observation period of 2014-2018. The analytical tool used is: Multiple Regression Analysis, Correlation Analysis, t Test and F Test. The results of this study indicate that the influence of individual and simultaneous significance of independent variables consisting of: Number of Taxpayers, Building Area, and Land Area has a significant effect on PBB Revenue in Berau Regency. So the hypothesis which states that the alleged number of taxpayers, building area, and land area has a significant effect on the receipt of land and building tax (PBB) in Berau Regency can be accepted. The basis for calculating the amount of PBB owed is the sale value of the tax object (NJOP) on the relevant tax object, there is often an imbalance in the amount of PBB that must be paid due to the location of the tax object and the amount / extent of the tax object concerned, it is recommended to the relevant agencies in terms of This Regional Government of Berau Regency through the Dinas Pendapatan Daerah Kabupaten Berau is able to formulate an NJOP assessment system that better reflects the sense of community justice and meets the principle of accountability (besides being accountable), in addition it is necessary to update tax object data owned by taxpayers regularly, so that can be seen the current tax object conditions so that the NJOP can be adjusted.